Arah dan Komponen Pokok Pelayanan Bimbingan Konseling di Sekolah - Ramadhani, Rahma; Amanah, Siti; Kurnia, Dewi (Universitas Muria Kudus, 2023)
Students have potentials that can be developed and material, spiritual needs that must be met. Guidance and Counseling in schools is a form of educational activity to achieve educational goals. This study uses the method of literature review or literature study. This technique is used with the aim of uncovering various theories related to the problem under study as reference material for discussing research results. In this study it was found that the direction of Guidance and Counseling services is to develop the potential of students according to the stages and tasks of their development. Educational efforts in general constitute the implementation of development services for students. In educational units, educators and educational staff have a dominant role in implementing the development of students. Guidance and counseling functions as a service provider to students so that each student can develop optimally so that they become whole and independent individuals.